Making (Anti)Modern Childhood: Producing and Consuming Toys in Late Victorian Canada - Hutchinson, Braden (Scientia Canadensis, 2013)
Prior to the First World War much of Canada’s toy supply came from Germany. When the guns of August sounded in 1914, Canadian consumers found themselves in the midst of a shortage of mass produced toys, dubbed the ‘toy famine’ in the popular press. Two incompatible solutions ultimately arose to deal with this problem of consumer demand and industrial supply. Middle class women, drawing on their work over the preceding decades distributing and producing toys for philanthropic means and the discourse of the conditioned child, turned to craft production using the labour of returned soldiers to refurbish second hand playthings and produce new ones as artisans. Canadian manufacturers, with the support of the state, pursued a policy designed to industrialize toy production in Canada for competition at home and abroad. In some cases, one group openly resisted the efforts of the other. Ultimately, these two visions made possible a debate about modernity and the role of industrial technology in Canadian family life and consumer culture.